Implementasi Kepemimpinan Berbasis Nilai Budaya Islam dan Budaya Lokal - Faiqoh Ghonim; M. Imamul Muttaqin (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
Leadership based on the values of Islamic culture and local culture is a leadership concept that integrates universal values from Islamic teachings with local wisdom present in society. In this context, leadership emphasizes not only managerial skills but also moral aspects, ethics, and social responsibility aligned with religious teachings and local customs. This article aims to explore the concept and implementation of leadership based on Islamic and local cultural values, as well as the challenges faced in its application. Leadership in Islam stresses the principles of justice, wisdom, and simplicity, which are reflected in the behavior of Prophet Muhammad (SAW) and his companions, while local culture provides a context that strengthens social relations and solidarity within the community. Through a literature study, it is found that the application of leadership based on these cultural values can enhance interpersonal relationships, strengthen moral integrity, and create a harmonious work environment in various organizations, both in education and government sectors. However, effective implementation requires a deep understanding of the balance between religious teachings and local wisdom in the changing social context. Therefore, it is essential to adapt these leadership principles according to the dynamics of society without disregarding the core values inherent in both cultures.